Analysis of the Influence of the Role of Influencers on Increasing Income in Liberica - Utari, Marti; Sari, Diah Novita; Rahmi, Lailatur; Devani, Ferizka Tiara; Mardiana, Mardiana (Utan Kayu Publishing, 2024)
The role of influencers is a successful marketing strategy because in the digital era, users choose interesting content from influencers and people they follow over advertising and frequent use of social media. This research aims to determine